DEVELOPMENT OF AN INVENTORY ENCYCLOPEDIA OF FERN TYPES BASED ON LOCAL POTENTIAL EXPLORATION IN BIANG ROSAN VILLAGE TOWARDS LEARNING INTEREST IN THE MATERIAL OF PTERIDOPHYTA AT SMAN 3 SANGGAU - Kurniawan, FX Evan; Herditiya, Herditiya (Universitas Lancang Kuning, 2024)
This research aims to determine the validity, practicality and effectiveness of an encyclopedia inventory of fern types based on local potential in Biang Rosan Hamlet on interest in learning about Pteridophyta material at SMA Negeri 3 Sanggau. The research method used is research and development (Research and Development) which uses the ADDIE research plan with steps, namely; (1) analysis (analyze), (2) planning (design), (3) development (development), (4) implementation (implementation), (5) evaluation (evaluation). The subjects of this research were 6 development subject validators and 30 trial subjects. The instruments used in this research were validation sheets, questionnaires and tests. The research results are; (1) the validity of the encyclopedia inventory of fern types in Biang Rosan Hamlet by media expert validators and material experts obtained a result of 84% with very valid criteria, (2) the practicality of the encyclopedia inventory of fern types in Biang Rosan Hamlet obtained a result of 91% with the criteria very practical, (3) the effectiveness of the fern encyclopedia in Biang Rosan Hamlet was obtained by learning results with an N-gain value of 0.72 with high criteria. Meanwhile, with the results of interest in learning using the interest in learning questionnaire, results were obtained at 90% with very practical criteria. Based on the research results, the media encyclopedia inventory of types of ferns in Biang Rosan Hamlet is very practical and effective to use.